2023
DOI: 10.1002/adma.202211277
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Composite Self‐Sorted Supramolecular Gel Noodles

Abstract: Multicomponent supramolecular systems can be used to achieve different properties and new behaviors compared to their corresponding single component systems. Here, we use a twocomponent system, showing that a non-gelling component modifies the assembly of the gelling component, allowing access to co-assembled structures that cannot be formed from the gelling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Hence, at a high pH, we have a self-sorted micellar system with two co-existing populations. We highlight that this is not always the case; we have recently shown that two structurally dissimilar functionalized dipeptides form mixed micelles at a high pH . We also note that due to operational issues, the cryo-TEM data were collected around 1 year after sample formation, implying that there is no kinetic trapping occurring.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Hence, at a high pH, we have a self-sorted micellar system with two co-existing populations. We highlight that this is not always the case; we have recently shown that two structurally dissimilar functionalized dipeptides form mixed micelles at a high pH . We also note that due to operational issues, the cryo-TEM data were collected around 1 year after sample formation, implying that there is no kinetic trapping occurring.…”
Section: Resultsmentioning
confidence: 90%
“…We highlight that this is not always the case; we have recently shown that two structurally dissimilar functionalized dipeptides form mixed micelles at a high pH. 29 We also note that due to operational issues, the cryo-TEM data were collected around 1 year after sample formation, implying that there is no kinetic trapping occurring. An interesting case was observed for one case where we were able to observe the formation of nanotubes from (L,D)-2NapFF.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among supramolecular assemblies of small molecules, peptide assemblies have received considerable research attention over the last few decades. Therefore, it is not surprising that peptide assemblies formed by EISA have become the most explored molecular platform for various applications since the demonstration of the EISA of small molecules . The first example of EISA in a living organism is the use of EISA of peptides to inhibit the growth of bacteria .…”
Section: Intracellular Peptide Assemblies Formed By Eisamentioning
confidence: 99%
“…[33] In this work, we aim to examine the effect of varying micellar agreements on calcium-bridged cross-linked gel, also known as "gel noodles." [34][35][36]…”
Section: Introductionmentioning
confidence: 99%